1978
DOI: 10.1088/0022-3727/11/4/018
|View full text |Cite
|
Sign up to set email alerts
|

The pressure and temperature dependence of the static permittivity and density of heptanol isomers

Abstract: The static relative permittivity and density of 1-heptanol, 3-heptanol, 3-methyl-2-hexanol, 2-methyl-2-hexanol have been measured as a function of pressure up to 3.5 kbar and from -30 degrees to 100 degrees C. The static relative permittivity has been observed to be a sensitive function of pressure, temperature and the isomeric structure of the alcohol. The Kirkwood dipole correlation factor g has been calculated from the experimental results and its pressure and temperature dependence has been discussed in te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
39
2

Year Published

1982
1982
2011
2011

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 12 publications
(13 reference statements)
0
39
2
Order By: Relevance
“…24 Johari and Dannhauser 5 also found that process II especially at lower temperatures was of the Davidson-Cole type. 25 This work was extended by Vij et al 12,13 to an investigation of four heptanol isomers (1-heptanol, 3-heptanol, 3-methyl-2-hexanol, and 2-methyl-2-hexanol) who investigated these liquids in the frequency range of 20 Hz to 6 MHz and temperatures from 373 K to 243 K. Since their low frequency measurements were limited to 20 Hz only, they did not observe the non-Arrhenius nature of the dominant process at the lowest temperatures. The nature of the dominant process was of the Debye-type in 1-heptanol.…”
Section: Introductionmentioning
confidence: 76%
See 4 more Smart Citations
“…24 Johari and Dannhauser 5 also found that process II especially at lower temperatures was of the Davidson-Cole type. 25 This work was extended by Vij et al 12,13 to an investigation of four heptanol isomers (1-heptanol, 3-heptanol, 3-methyl-2-hexanol, and 2-methyl-2-hexanol) who investigated these liquids in the frequency range of 20 Hz to 6 MHz and temperatures from 373 K to 243 K. Since their low frequency measurements were limited to 20 Hz only, they did not observe the non-Arrhenius nature of the dominant process at the lowest temperatures. The nature of the dominant process was of the Debye-type in 1-heptanol.…”
Section: Introductionmentioning
confidence: 76%
“…Table IV lists the dielectric relaxation time of the dominant process (process I for the data at P ∼ 0.1 MPa), τ II and the Kirkwood correlation factor, g, at a temperature of 258 K. The calculated values of Kirkwood correlation factor, g, and the relaxation times for a selected set of temperature and pressure are also listed. In order to calculate the g-factor at a pressure of 200 MPa and temperature of 258 K density for 5-methyl-2-hexanol was extrapolated from its close isomer which was already reported by Vij et al 12 From a perusal of Table IV (Table III), it would not therefore be correct to state that τ I is governed by hydrogen bonding alone and τ II corresponding to process II, refers to the dynamics of the alkyl chains and the latter process only contributes to the structural relaxation. Based on these experimental findings, it is reasonable to assert that both processes contribute to the structural relaxation.…”
Section: B Structural Relaxationmentioning
confidence: 99%
See 3 more Smart Citations